The implications of government funding on non-profit organizational behaviour: a resource depenence perspective - Macedo, Isabel Maria (2005)
It has been generally accepted that there has been an extensive sharing of responsibility between the state and non-profit organisations (NPOs) in order to accomplish public purposes. As a result, the relationship between both sectors, and the degree of dependency of NPOs on the state for resources has been acknowledged as a critical issue within social and public policy debates. However, the intensity of this debate has not been matched by a search for empirical evidence, which might assist in assessing the nature and extent of this dependency as well as the implications, either for the non-profit sector or the state. Therefore, this paper seeks to address this gap in the literature by providing empirical evaluation of the nature and scope of non-profit organisations dependency on the state for resources regarding the Portuguese case. It also analyses the implications that different types of resource dependencies might have on the organisational behaviour of these organisations.